2016
DOI: 10.1590/1980-5373-mr-2015-0784
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Crack Propagation in Cement PMMA: Comparison of Different Criteria

Abstract: Modelling of a crack propagating through a finite element mesh under mixed mode conditions is of prime importance in fracture mechanics. In this paper, three different crack growth criteria and the respective crack paths prediction in the cement mantle of the reconstructed acetabulum are compared. The maximum tangential stress (MTS) criterion, the minimum strain energy density (MSED) criterion and the new general fracture criterion based on the energy release rate G(θ) are investigated using advanced finite el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this study the mechanical properties of the components of the femoral prosthesis were taken from previous work [5,7,9,13,23].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the mechanical properties of the components of the femoral prosthesis were taken from previous work [5,7,9,13,23].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In the cemented femoral prosthesis, the structural resistance of the THP is provided by the cement, which must withstand the mechanical stresses that can potentially lead to the generation and propagation of cracks and the possible failure of the entire THP structure [3,4]. PMMA has important micro structural heterogeneities such as cavities, and its elastic behavior is greatly affected by the presence of defects that may imply its weakening and cause failure [4,5]. In areas of high concentrations of stress and due to the presence of micro cracks appear after crushing cavities due to patient movement; these micro cracks grow and weld to each other until they form a macro fissure that propagates until the total removal of the prosthesis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…There are several techniques are used to obtain stress intensity factors (SIFs) in homogeneous and inhomogeneous materials, such as the displacement correlation technique (DCT) [20], the J* k -Integral [21,22] and the modified crack-closure integral (MCC) [23]. The displacement extrapolation technique (DET) used to calculate the SIFs K I and K II for homogeneous materials [24][25][26][27] is modified to calculate the SIFs for non-homogeneous materials, in present study. For the FGMs, the SIFs K I and K II can be expressed as follows:…”
Section: Determination Of Fracture Parameters 21 Numerical Evaluatiomentioning
confidence: 99%
“…This risk is due to the low tensile strength of the cement. Other numerical work [12] showed that the existence of microcavity promotes the initiation and propagation of cracks of the cup of cement. The stress intensity factor is strongly influenced by the nature of the bone-cement interface, cement-implant.…”
mentioning
confidence: 96%
“…Several research works were dedicated to the analysis of the damage of the cement which is largely responsible for the loosening of the total hip prosthesis. So Mr. Bouziane et al [10] Zouambi et al [11], Benouis et al [12] analysed by the finite element method the effect of the microcavity on the behaviour of hip cement. These authors showed that these defects weaken the material due to notch effect and interaction.…”
mentioning
confidence: 99%